Seroepidemiology of Chlamydia trachomatis Infection in the General Population of Northern China: The Jidong Community Cohort Study - Shui, Jingwei; Xie, Dongjie; Zhao, Jianhui; Ao, Cailing; Lin, Hongqing; Liang, Yuanhao; Wang, Haiying; Dai, Yingchun; Tang, Shixing (Frontiers in Microbiology, 2021)
Longitudinal serological study to investigate the seropositive frequency, incidence and antibody dynamics of C. trachomatis infection in the general population of China is urgently needed in order to optimize the strategies for surveillance and precise prevention of C. trachomatis infection. This longitudinal study enrolled 744 subjects aged 18 to 65 years from Jidong Community of Northern China from 2014 to 2018. Seropositive frequency, incidence and reinfection of C. trachomatis were determined by detecting antibody against C. trachomatis Pgp3 using “in-house” luciferase immunosorbent assay (LISA). The dynamic of anti-Pgp3 antibody was analyzed using Generalized Estimating Equation model. The overall Pgp3 seropositive frequency among 18-65-year-old population was 28.1% (95% CI 24.9-31.5), and significantly increased from 12.0% in those aged 18-29 years to 48.6% in the 60-65 years old. The seropositive frequency was slightly higher in women than in men (31.3% vs 25.4%) without statistical significance. The C. trachomatis incidence and reinfection rate were 11 and 14 per 1000 person-year, respectively, and showed no significant difference with respect to age, gender, ethnicity, marital status, and education levels. Furthermore, anti-Pgp3 antibody remained detectable in 93.3% (195/209) of the seropositive subjects during the 5 years of follow up. The overall decay rate for anti-Pgp3 antibody for CT-infected persons was -0.123 Log2 RLU/year, which was dramatically slower than in CT new infection (-3.34 Log2 RLU/year) or reinfection (-1.1 Log2 RLU/year). In conclusion, at least one quarter of the people aged 18-65 years have been infected with C. trachomatis over their lifetime while all age groups are susceptible to C. trachomatis infection in the community of Northern China. Therefore, comprehensive prevention strategies are urgently needed.